IMPLEMENTASI PROGRAM TAHSIN UNTUK PENGEMBANGAN KUALITAS BACAAN AL-QUR'AN SISWA - Miftahul Faoz; Rahmat Setiawan (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
The Qur'an demands a standard of authentic recitation through mastery of makhraj, tajwid, and tartil, however, in the Kalijaga Banjarnegara Mosque, significant variations in recitation quality are still found amidst the limited traditional informal rural education facilities. This study aims to describe the implementation of the tahsin program through a qualitative approach with a comprehensive case study design carried out from January to February 2026. The systematic research steps involved purposive sampling techniques for tahsin teachers, takmir administrators, and students, with data collection procedures through direct participant observation, in-depth interviews, and authentic documentation studies which were then analyzed using the interactive model of Miles, Huberman, and Saldaña. The research findings show that the implementation of the tahsin program includes multilevel curriculum planning, the talaqqi method in the halaqah system, and regular achievement evaluation. Real obstacles were identified in the form of low motivation in 60% of beginner students and an absenteeism rate of up to 25% due to family schedule conflicts. The adaptive solutions implemented included 5-10 minutes of individual cognitive guidance per student, a motivational reward system, and intensive coordination with parents through a WhatsApp group. The main conclusion confirms that the tahsin program at the Kalijaga Mosque has proven effective in improving the quality of students' Quran reading when supported by consistent educators, differentiated method adaptations, and strong communication synergy between the institution and families. ABSTRAK Al-Qur'an menuntut standar bacaan sahih melalui penguasaan makhraj, tajwid, dan tartil, namun di Mushola Kalijaga Banjarnegara masih ditemukan variasi kualitas bacaan yang signifikan di tengah keterbatasan sarana pendidikan informal pedesaan yang bersifat tradisional. Penelitian ini bertujuan mendeskripsikan implementasi program tahsin melalui pendekatan kualitatif dengan desain studi kasus komprehensif yang dilaksanakan pada periode Januari hingga Februari tahun 2026. Langkah penelitian secara sistematis melibatkan teknik purposive sampling terhadap guru tahsin, pengurus takmir, serta siswa, dengan prosedur pengumpulan data melalui observasi partisipan langsung, wawancara mendalam, dan studi dokumentasi autentik yang kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña. Temuan riset menunjukkan bahwa pelaksanaan program tahsin mencakup perencanaan kurikulum bertingkat, metode talaqqi dalam sistem halaqah, serta evaluasi capaian secara rutin. Teridentifikasi hambatan nyata berupa rendahnya motivasi pada 60% siswa kategori pemula dan tingkat ketidakhadiran mencapai 25% akibat konflik jadwal keluarga. Solusi adaptif yang diterapkan meliputi bimbingan kognitif individual berdurasi 5-10 menit per siswa, sistem pemberian hadiah motivasional, serta koordinasi intensif bersama wali murid melalui grup komunikasi WhatsApp. Simpulan utama menegaskan bahwa program tahsin di Mushola Kalijaga terbukti efektif dalam meningkatkan kualitas bacaan Al-Qur'an siswa apabila didukung konsistensi pendidik, adaptasi metode yang terdiferensiasi, serta sinergi komunikasi yang sangat kuat antara pihak lembaga dengan keluarga.